Quarry in the black - Collins, Max Allan (Hard Case Crime book, 2016)
With a controversial presidential election just weeks away, Quarry is hired to carry out a rare political assignment: kill the Reverend Raymond Wesley Lloyd, a passionate Civil Rights crusader and campaigner for the underdog candidate. But when a hate group out of Ferguson, Missouri, turns out to be gunning for the same target, Quarry starts to wonder just who it is he's working for.--page 4 of cover.